Cumulative exposures to glycaemia and lipids are associated with coronary artery disease in type 1 diabetes: a call for action - Rebecka Bergdal; Valma Harjutsalo; Per-Henrik Groop; Stefan Mutter; on behalf of the FinnDiane Study Group (Cardiovascular Diabetology)
Abstract Background Hyperglycaemia and dyslipidaemia are well-known risk factors for coronary artery disease (CAD) in type 1 diabetes. The impact of long-term cumulative exposure to these risk factors is less explored. We investigated the relationship between cumulative glycaemic and lipid exposure and CAD in individuals with type 1 diabetes. Methods This longitudinal study included 3495 adults with type 1 diabetes from the FinnDiane cohort, without end-stage kidney disease and no history of CAD or stroke at the study baseline. Total cumulative glycaemic exposure (CGEtot) and cumulative hyperglycaemic exposure (CGEhg), accounting only for time spent above an HbA1c of 53 mmol/mol (7%), were calculated from diabetes diagnosis. Results During a median follow-up of 19.38 years, 534 participants had their first-ever CAD event. CGEhg (odds ratio 1.03 [95% CI 1.02–1.05], p < 0.001) and cumulative exposure to LDL cholesterol, triglycerides, and non-HDL cholesterol all significantly increased the odds for incident CAD. The highest tertile of CGEhg associated with a twofold odds increase for incident CAD. CGEtot was not significantly associated with CAD after adjusting for cumulative lipid exposure. Conclusions Both hyperglycaemia and dyslipidaemia are independently associated with CAD in type 1 diabetes. These findings emphasize the importance of reaching an HbA1c below 53 mmol/mol (7%) and minimizing lipid exposure, as well as calling on health care professionals to not settle for suboptimal care, but to continue their support and encouragement towards better management of diabetes. Graphical Abstract